Effects of carrion decomposition on litter arthropod assemblages. (4th July 2020) - Sawyer, Samantha J.; Bloch, Christopher P.
Abstract : Many organisms contribute to the decomposition of carrion. For arthropods, many studies focus on the necrophagous community, those directly consuming carrion. Necrophagous arthropods use carrion as a shelter or food source. Therefore, carrion generally increases the abundance and biodiversity of necrophagous species. However, it is unclear if carrion has similar effects on detrital communities. This study examines changes in community structure and composition of necrophilous and detrital communities over the course of decomposition. Five pig head carrion were placed at least 7 m apart under cages in temperate mixed forest. Leaf litter was sampled 0 m, 1.5 m, and 3 m from each carrion weekly during summer, and monthly during autumn, until the first frost. Arthropods were extracted from leaf litter by using Berlese funnels. At the carrion site, necrophagous insects increased in abundance, species richness, and Shannon diversity during decomposition, and all decreased after dry decay. Detritus arthropods displayed a sharp increase in abundance during advanced decay, decreasing during dry decay, and a general increase over time for species richness and diversity. In conclusion, carrion can influence the surrounding, non‐necrophagous arthropod community, highlighting the need to investigate carrion effects beyond typical necrophagous species to have a more holistic understanding of carrion ecology. Abstract : At the carrion site, necrophagous insects increased in abundance, species richness, and Shannon diversity during decomposition, and all decreased after dry decay. Detritus arthropods displayed a sharp increase in abundance during advanced decay, decreasing during dry decay, and a general increase over time for species richness and diversity. This study shows carrion can influence surrounding, non‐necrophagous arthropod community, highlighting the need to investigate carrion effects beyond typical necrophagous species to have a more holistic understanding of carrion ecology.